Confined chromophores in tobacco mosaic virus to mimic green fluorescent protein. Issue 82 (1st September 2015) - Zhou, Quan; Wu, Fengchi; Wu, Man; Tian, Ye; Niu, Zhongwei
Abstract : Grafting green fluorescent protein-like chromophores in the 4 nm channel of tobacco mosaic virus greatly enhances its fluorescence emission. Abstract : Due to the nano-confinement effect, grafting green fluorescent protein-like chromophores on the interior surface of tobacco mosaic virus can greatly enhance its fluorescence emission in various solvents.